HOW TO MAKE ECOPRINT ON MASK IN THE CONTEXT OF COVID-19 PREVENTION BASED ON ECO GREEN at HIRZU MILLATI ISLAMIC BOARDING SCHOOL, SINGOCANDI KUDUS - Rohmatun Nafi'ah; Arina Hafadhotul Husna (Jurnal Pengabdian Kesehatan, 2021)
Along with the increasing number of Covid-19 cases in Kudus Regency, which greatly affects people's lifestyles. For this reason, STIKES Cendekia Utama Kudus performs Community Service. This community service aims to provide soft skill training in making Ecoprints on Masks as an effort to prevent Covid-19 based on Eco Green, because wearing masks is one of the efforts in preventing Covid-19. In addition, by providing English language training on "Procedure text" and practicing speaking skills on procedures for making ecoprint masks. The target of this service activity is the female students of "Hirzu Millati Islamic Boarding School", Singocandi Kudus. This activity was carried out on Friday, January 22, 2021. The implementation of this activity was carried out in 3 stages; The first stage is planning, preparation and the last stage is the implementation of activities. In the implementation of the activities, the method used is the lecture method with presentation techniques and direct practice of making Ecoprints on Eco Green-based masks and presenting directly through speaking. The results of this community service activity are very good, the students of "Hirzu Millati Islamic Boarding School" are getting more creative, productive and innovative in creating masks during the making of Ecoprints from natural materials based on Eco Green. Santriwati is also active and dares to come forward to present in “Speaking English” The procedure for making ecoprint masks, they are very enthusiastic about the activities that have been carried out. This activity has a positive impact on the students.